1999
DOI: 10.1046/j.1365-3148.1999.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of transfusion‐transmitted cytomegalovirus infection

Abstract: Cytomegalovirus (CMV) is a double-stranded DNA virus which can be transmitted by blood transfusion. Its seroprevalence in adults ranges from 40% to 100% depending on geographical and socioeconomic conditions. Seropositive individuals have latent CMV infection with viral DNA present in peripheral blood leucocytes. CMV can be associated with considerable morbidity and mortality in susceptible individuals, e.g. CMV-seronegative bone marrow allograft patients. Evidence, from a number of reports, suggests that prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 54 publications
1
59
0
6
Order By: Relevance
“…Since CMV infection was significantly associated with poor response to platelet transfusion, the use of PCs from seronegative donors and/or leukocyte depletion of PCs are strongly recommended in seronegative HSCT donor/recipient pairs. 31 Our study clearly shows that alloimmunization greatly reduced the efficacy of platelet transfusions. On this basis, measures effective in preventing alloimmunization, such as the reduction of leukocytes by filtration and ultraviolet irradiation of PCs, 3 are mandatory in this clinical setting.…”
Section: Leukemiamentioning
confidence: 59%
“…Since CMV infection was significantly associated with poor response to platelet transfusion, the use of PCs from seronegative donors and/or leukocyte depletion of PCs are strongly recommended in seronegative HSCT donor/recipient pairs. 31 Our study clearly shows that alloimmunization greatly reduced the efficacy of platelet transfusions. On this basis, measures effective in preventing alloimmunization, such as the reduction of leukocytes by filtration and ultraviolet irradiation of PCs, 3 are mandatory in this clinical setting.…”
Section: Leukemiamentioning
confidence: 59%
“…[61][62][63][64] However, some centers give only CMV-negative blood products for patients undergoing HSCT where both the patient and donor are CMV-negative. 65 The indications for fresh-frozen plasma in AA patients are the same as those in the general transfusion guidelines. 53 …”
Section: Transfusion Therapymentioning
confidence: 99%
“…The source of CMV in these cases is unclear. Primary CMV infection is unlikely to account for all these cases, since the annual incidence of new infection is around 1% in adults, 20 and because all patients were restricted in their social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been suggested that leucodepletion at source may substitute for CMV-negative blood products for BMT recipients (reviewed in Ref. 20), although this is yet to be tested in a prospective trial. It will therefore be interesting to see the impact of leucodepletion at source on the incidence of CMV DNA positivity following allografting.…”
Section: Discussionmentioning
confidence: 99%